The mixed-status community as analytic framework to understand the impacts of immigration enforcement on health - Lopez, William D.; Castañeda, Heide (Social science & medicine (1982), 2022)
Social scientists are increasingly interested in the detrimental health impacts of immigration enforcement, including surveillance, arrest, detention, and deportation. In most empirical research—as well as the legal process itself—the family or household serves as the social unit for understanding ripple effects of immigration enforcement beyond the individual. While the mixed-status family analytic framework foregrounds the experiences of millions of individuals and valuably extended immigration scholarship to move beyond its heavy focus on individual behavioral choices, we argue that a continued reliance on the family as an analytic framework reproduces normative conceptualizations of kinship and care, obscures how the process of illegality is mediated by empire, racism, and (hetero)sexism, and risks reproducing narratives about the “deserving” immigrant. We propose the mixed-status community as an analytic framework to better understand the detrimental health impacts of immigration enforcement by accounting for the synergistic influence of 1) a fuller range of social and intimate relationships; 2) spatial arrangements of risk; 3) presumptions of immigration status; and 4) racialization of immigration law and enforcement practices. We draw on a case study of an immigration raid as well as contemporary examples to illustrate the added value of this analytic framework. •The frame of “mixed-status community” may better explain how deportation harms health.•Immigration enforcement harms health across a range of relationships.•Community members avoid public spaces and places when they fear arrest.•Immigration enforcement is rooted in racial profiling.